1991
DOI: 10.1002/app.1991.070420828
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen permeation through Teflon–PFA tubing into flowing helium

Abstract: SYNOPSISThe permeability coefficient for oxygen diffusing through a sample of Teflon-PFA tubing has been determined experimentally. The source of the diffusing oxygen was ambient air surrounding a 1.835 m length of PFA tubing. Pressurized high purity helium was directed through the center of the PFA tubing. Oxygen permeating from the low pressure ambient air source, through the PFA tubing, and into the flowing pressurized helium was observed in the effluent gases as they passed through a trace oxygen analyzer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As mentioned above, we expect that polar sites are formed due to the leakage of O 2 into the reactor along with the formation of free radicals due to crushing silica by the rocking action of the reactor . Previous reports have shown that hot H 2 gas is capable of reducing oxidized carbon surfaces .…”
Section: Resultsmentioning
confidence: 89%
“…As mentioned above, we expect that polar sites are formed due to the leakage of O 2 into the reactor along with the formation of free radicals due to crushing silica by the rocking action of the reactor . Previous reports have shown that hot H 2 gas is capable of reducing oxidized carbon surfaces .…”
Section: Resultsmentioning
confidence: 89%
“…(6)] and then plotted in Figure 4 as V B/AÁDp versus t according to eq. (7). The points are experimental data and the solid line represents linear regression from longer times.…”
Section: Resultsmentioning
confidence: 99%
“…A great deal is known about the purity, mechanical, and thermal properties of PTFE and its copolymers, [3][4][5] but less information is available regarding their permeation characteristics. Although some permeation studies have been performed, [6][7][8][9][10][11][12][13] many have focused on fluoropolymers for membrane applications. [11][12][13] Because PFA is a semicrystalline polymer, its properties can be strongly affected by the processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the melt-processable fluoropolymers, tetrafluoroethylene−perfluoroalkoxy copolymers, often abbreviated simply as PFA, have the highest service temperature and therefore have been used broadly in semiconductor fabrication. , While much is known about the purity, mechanical, and thermal properties of polytetrafluoroethylene (PTFE) and its copolymers, less information is available regarding their permeation characteristics. Some permeation testing has been performed on PFA, but these studies have not addressed two of the most widely used process chemicals, hydrochloric acid and ammonium hydroxide. Since the active ingredient in both of these aqueous chemicals is a dissolved gas, there have been concerns about unwanted permeation potentially causing cross-contamination or corrosion.…”
Section: Introductionmentioning
confidence: 99%